THE RELATIONSHIP BETWEEN DEPRESSION, ANXIETY, STRESS AND SELF HARM AMONG COLLEGE STUDENTS: A CROSS-SECTIONAL SURVEY: Depression, Anxiety, Stress And Self Harm - Abbasi, Dr Najam Ul Hasan; Raza, Asad; Khurshid, Maryam; Ansari, Muhammad Ibrahim (Pakistan Armed Forces Medical Journal, 2018)
Objective: The aim of present study was to assess the relationship between depressions, anxiety, and stress andself-harm. The study also aimed at finding gender and educational year differences on the basis of main studyobjective.Study Design: Cross sectional study.Place and Duration of Study: Colleges of Jhelum, Jhelum from Sep 2016 to Feb 2017.Material and Methods: Deliberate Self-harm Inventory was used to measure self-harm behaviors, whileDepression, Anxiety and Stress Scale was used to assess depression, anxiety and stress among adolescents. Datawas analyzed using SPSS 20.Results: A sample of 400 was drawn by sensitivity and specificity calculator using consecutive non probabilitysampling, out of which 322 participants (128 male and 194 female students) from Jehlum, Punjab completed thesurvey. The data was collected over the period of six months and then analyzed. Results indicated that a slightlynegative correlation exist between depressions, anxiety, and stress and self-harm (p